Is Namalycastis abiuma (Grube, 1871) (Annelida: Nereididae) restricted to its type-locality? Evidence from morphological and molecular data - Paulo Ricardo Alves; Christopher J. Glasby; Paulo Cesar Paiva; Cinthya Simone Gomes Santos (Ocean and Coastal Research)
Namalycastis abiuma has been recorded as a worldwide distributed species, found in most tropical and subtropical mangroves and estuarine environments. However, this status has been questioned in several publications, which indicate that several distinct species are being identified under the name N. abiuma. In this study, we perform a morphological analysis, along with a series of species delimitation tests and a phylogenetic analysis—using the molecular marker 16S—to evaluate whether analyzed populations previously identified as Namalycastis abiuma belong to the same species. We used sequences from the GenBank database in the analysis, as well as six newly sequenced specimens collected from the coast of Brazil, two of them from the N. abiuma type-locality. For species delimitation, we applied the Generalized Mixed Yule Coalescent (GMYC), the Assemble Species by Automatic Partitioning (ASAP), and the Multi-rate Poisson Tree Processes (mPTP) tests. Results from GMYC and ASAP suggest that Namalycastis abiuma may be endemic to the type-locality and that all other populations studied represent a second distinct species. However, mPTP indicates that all Namalycastis species included should be grouped into one single species. The mPTP results seem to be biased due to data limitation as it showed poor statistical support. Our morphological data, especially on the shape and dentition of the sub-neuroacicular falciger blades, support the GMYC and ASAP results, suggesting restricted endemism for Namalycastis abiuma. Based on these results, we conclude that N. abiuma is restricted to its type-locality and we provide a description of a new species, Namalycastis lanai sp. nov. occurring in Brazilian waters from 22°S to 27°S, including, at its southern range, an overlap with N. abiuma at Florianópolis. Finally, we provide a key to all Namalycastis species found in Brazil.